2021
DOI: 10.3390/ijerph182312484
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Determinants of Integrated Service Delivery for Intimate Partner Violence and Mental Health in Humanitarian Settings

Abstract: Inter-agency guidelines recommend that survivors of intimate partner violence in humanitarian settings receive multisectoral services consistent with a survivor-centered approach. Providing integrated services across sectors is challenging, and aspirations often fall short in practice. In this study, we explore factors that influence the implementation of a multisectoral, integrated intervention intended to reduce psychological distress and intimate partner violence in Nyarugusu Refugee Camp, Tanzania. We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…For example, while a study from Northern Uganda found that gender equitable attitudes mitigated the relationship between IPV victimization and mental illness [ 29 ], analyses from Nigeria revealed that survivors of IPV who believed IPV was acceptable in some situations exhibited lower mental distress [ 26 ]. Third, this Special Issue offers actionable guidance for practitioners by evaluating promising intervention approaches [ 30 , 34 ], reviewing the evidence on what works to prevent IPV and subsequent psychological distress [ 35 , 36 ], and highlighting determinants for the successful implementation of integrated interventions that address IPV and mental health in tandem [ 37 ]. Importantly, all papers in this Special Issue advance the knowledge base on how to understand and address IPV and mental health in LMICs, ultimately strengthening our ability to make progress toward the SDGs.…”
mentioning
confidence: 99%
“…For example, while a study from Northern Uganda found that gender equitable attitudes mitigated the relationship between IPV victimization and mental illness [ 29 ], analyses from Nigeria revealed that survivors of IPV who believed IPV was acceptable in some situations exhibited lower mental distress [ 26 ]. Third, this Special Issue offers actionable guidance for practitioners by evaluating promising intervention approaches [ 30 , 34 ], reviewing the evidence on what works to prevent IPV and subsequent psychological distress [ 35 , 36 ], and highlighting determinants for the successful implementation of integrated interventions that address IPV and mental health in tandem [ 37 ]. Importantly, all papers in this Special Issue advance the knowledge base on how to understand and address IPV and mental health in LMICs, ultimately strengthening our ability to make progress toward the SDGs.…”
mentioning
confidence: 99%
“…In terms of implementation feasibility, a coordinated approach to service delivery, such as that required to organize and deliver integrated NCD care, is not new to humanitarian actors. For instance, there is experience in arranging multisectoral integrated service delivery for survivors of intimate partner violence ( Greene et al, 2021 ).…”
Section: Knowledge On the Feasibility And (Cost)-effectiveness Of Int...mentioning
confidence: 99%
“…Enhancing support networks and outreach services are critical to preventing a descent into homelessness or abject poverty . In such circumstances, as The Banyan's efforts reveal, the role of social work practitioners, alongside health professionals, is critical to a crisis intervention team (Greene et al, 2018;Reza Iravani & Majidi Parast, 2014). Social workers are in a unique position to provide both clinical services and coordinate interdepartmental liaison work, all embedded in a collaborative, justice and human rights framework.…”
Section: Role Of the Social Work Practitionermentioning
confidence: 99%